THE SPREAD OF FOODBORNE DISEASES AND THEIR PREVENTION (The Conference Hub, 2025)
Foodborne diseases are one of the major global public health concerns. According to the World Health Organization (WHO), millions of people suffer from these diseases every year, with children, pregnant women, and individuals with weakened immune systems being particularly vulnerable to severe consequences. These diseases are caused by various bacteria, viruses, parasites, and toxins.